KAJIAN KES: PEMBELAJARAN BERASASKAN KERJA PROGRAM TEKNOLOGI PENGURUSAN FASILITI MELALUI KOLABORASI POLITEKNIK DAN INDUSTRI - Ismail, Syamhanim; Mohamad, Mimi Mohaffyza; Mohd Faiz, Nur Sofurah (Online Journal for TVET Practitioners, 2018)
Work-based Learning(WBL) is one of the learning methods that combined two learning medium which is theoretical learning at the institutions and practical learning at the industry to produce graduate with high employability. This method has already implemented in developed county such as United States and United Kingdom, but it has just been introduced in the Malaysia education system. Work-based Learning method has been introduced in 2007 in the Community College Diploma programME and this implementation was discontinued and transferred to the Polytechnic in Advanced Diploma programme in 2010. The program using this method has expanded when the polytechnics decided to using WBL method in the Bachelor Degree programme. This paper discusses the outcome of a program that uses the CAL method in the Bachelor of Technology Management Facilities with Honors which is a collaboration between Sultan Salahudin Abdul Aziz Shah (PSA) and UEM Edgenta (UEM). The aim of this study is to explore the WBL elements through the relationship between Polytechnics and industry. This study was conducted using qualitative method in case study. The data collection process used is to use a random sampling method by selecting a study participant from the PSA and a research participant from UEM who are directly involved in this method to ensure that researchers obtain data rich in information. Data was obtained through a face-to-face semi-structured interview method. The findings of this case study show that there are two elements that influence PSA and UEM to work together, namely inspiration from community colleges and the appropriate WBL program offerings.